Exploring Facilitators and Barriers of Medically Tailored Meal Interventions for Patients Hospitalized With Acute Heart Failure: A Qualitative Study - Hassanieh, Ihab; Yoo, Sang Gune K.; Li, Jing; McKay, Virginia; Huffman, Mark D. (Journal of the American Heart Association, 2025)
Acute heart failure (AHF) is associated with high rehospitalization, morbidity, and mortality rates. Implementing medically tailored meal (MTM) interventions may help to optimize nutrition and improve outcomes for patients with AHF. This study aimed to explore facilitators and barriers to implementing an MTM intervention in a tertiary hospital. From August 2023 to October 2023, we conducted semistructured interviews with health care workers and patients with AHF at Barnes Jewish Hospital in Saint Louis, Missouri. The study used the updated Consolidated Framework for Implementation Research 2.0 to assess 5 domains: MTM characteristics, inner and outer settings, individual characteristics, and implementation process. Audio files were transcribed, and data were analyzed using inductive and deductive approaches. The sample (n=30) consisted of health care workers, including cardiologists (n=5), hospitalists (n=3), nurse practitioners (n=3) and dietitians (n=4), and patients hospitalized for AHF (n=15). Participants identified facilitators including perceived trust in MTM recommendations from providers, potential for improved health outcomes, necessity for dietary compliance, and availability of multidisciplinary teams for implementation. Barriers included the need for further research on MTM efficacy, logistical complexities of MTM implementation, implementation costs, limited funding, and lack of electronic medical record integration. Patient participants had limited knowledge about MTM interventions and highlighted the importance in choosing their prescribed meal options. This study identified facilitators and barriers to implementing an MTM intervention for patients with AHF in a tertiary hospital. Addressing these barriers with contextually relevant strategies could enhance the successful implementation of MTM programs.